Indian perspective of administrative culture - Surendra Kumar (2011)
The nature of political system in a society determines the quality and character of its administrative system. Bureaucracy is influenced by political, economic and socio-cultural environment and in turn, these factors are also influenced by administration. The object or target of administrative culture is public bureaucracy. Bureaucracy is a cohesive, well-organised and compact group with a network of continuing interactions. It is an instrument or arm of the government to operationalise programmes and policies meant for all-round development of the country. There is a strong need to identify the areas in administrative culture which have a bearing on the governance and development process. The article highlights the cultural traits of Indian bureaucracy and examines these against the backdrop of prevailing model of development. It offers suggestions for effective performance to ensure quality in governance and all-round development - Reproduced.
Keywords: Public administration